Плутовской роман XVI-XVII вв.: сборник : перевод / гравюры А. Дюрера - Дюрер Альбрехт (Фирма Арт, 1992)
Экземпляры: ф.3 (1993) / Инвентарный номер: 36826 / Цена: / Сис.шифр: 84(0)5 / Авт.знак: П 40 / ГРНТИ: 17.82.30 / ББК: 84(0)5